Organic Thin‐Film Transistors: Flexible Low‐Voltage Organic Complementary Circuits: Finding the Optimum Combination of Semiconductors and Monolayer Gate Dielectrics (Adv. Mater. 2/2015). (January 2015) - Kraft, Ulrike; Sejfić, Mirsada; Kang, Myeong Jin; Takimiya, Kazuo; Zaki, Tarek; Letzkus, Florian; Burghartz, Joachim N.; Weber, Edwin; Klauk, Hagen
<x xml:space="preserve">Abstract</x> The observation that n‐channel organic semiconductors perform better when deposited onto fluoroalkyl self–assembled monolayers (SAMs) while p‐channel semiconductors perform better on alkyl SAMs raises the question as to which SAM to employ in complementary circuits. As U. Kraft and co‐workers describe on page 207, the answer depends on the transistor's contact resistance and hence the channel length. Here, a signal delay of 3.1 μs is measured in ‐circuits based on transistors with a channel length of 1 μm. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>